2020
DOI: 10.1186/s13578-020-00450-y
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages inhibit adipogenic differentiation of adipose tissue derived mesenchymal stem/stromal cells by producing pro-inflammatory cytokines

Abstract: Background: Mesenchymal stem/stromal cells (MSCs) and macrophages are critical components in many tissue microenvironments, including that in adipose tissue. The close interaction between MSCs and macrophages modulates various adipose-related disease development. However, the effects of macrophages on the fate of MSCs remain largely elusive. We here studied the effect of macrophages on the adipogenic differentiation of MSCs. Methods: Macrophages were obtained from THP-1 cells treated with phorbol-12-myristate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Enhanced osteogenesis was also observed by several groups, they demonstrated that M1 macrophages promote osteogenesis in MSCs via the COX-2-PGE2 pathway (Guihard et al, 2012;Lu et al, 2017;Zhang et al, 2017;Nathan et al, 2019;Tang et al, 2019). Recently, the Shi group reported that macrophage-derived supernatants can inhibit the adipogenic differentiation of human adiposederived mesenchymal stem cells (hADSCs) in vitro, irrespective of the polarization status (M0, M1, or M2 macrophages) (Ma et al, 2020). In summary, macrophages also have an important influence on the differentiation ability of MSCs.…”
Section: Effect Of Macrophage On Mscmentioning
confidence: 78%
“…Enhanced osteogenesis was also observed by several groups, they demonstrated that M1 macrophages promote osteogenesis in MSCs via the COX-2-PGE2 pathway (Guihard et al, 2012;Lu et al, 2017;Zhang et al, 2017;Nathan et al, 2019;Tang et al, 2019). Recently, the Shi group reported that macrophage-derived supernatants can inhibit the adipogenic differentiation of human adiposederived mesenchymal stem cells (hADSCs) in vitro, irrespective of the polarization status (M0, M1, or M2 macrophages) (Ma et al, 2020). In summary, macrophages also have an important influence on the differentiation ability of MSCs.…”
Section: Effect Of Macrophage On Mscmentioning
confidence: 78%
“…Adipose-derived stem cells produce many molecules responsible for cell signaling, such as cytokines [29,74], growth factors [28,75], morphogens [76], chemokines [27,77], and extracellular vesicles [78][79][80], improving various cellular mechanisms. Interestingly, compared to BM-MSCs-the second most frequently considered MSCs for stem cell therapy-ASCs secrete more growth factors, and this feature increases their regenerative capacity [2,81].…”
Section: Adipose-derived Stem Cells Secretomementioning
confidence: 99%
“…In addition to bifunctional IL-2 and IL-6, adipose-derived stem cells secrete other cytokines with a well-defined pro-inflammatory (IL-7, IL-8, IL-9, IL-11, IL-12, IL-15, IL-17, interferon-gamma IFN-γ, IL-1β, and tumor necrosis factor-alpha TNF-α) or antiinflammatory (IL-1Ra, IL-4, IL-10, and IL-13) properties [29,44,89]. It has been shown that TNF-α and IL-1β secretion by macrophages mediates the inhibitory effect on ASCs adipogenesis, and also that combination of TNF-α or IL-1β with IFN-γ can enhance the immunomodulatory properties of ASCs mainly dependent on indoleamine 2, 3-dioxidase (IDO) or inducible nitric oxide synthase (iNOS) [74]. IFN-γ triggers ASCs to elicit immunosuppressive factors [90].…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…They produce various molecules that interact with other immune cells and tumor cells and further affect the progression in CRC (38). Under the influence of different cytokines and exosomes, three types of macrophages can be identified: naive M0, the M1 subtype with pro-inflammatory effects, and the M2 subtype with immunosuppressive effects (39,40), which promote or inhibit the progression of CRC.…”
Section: The Role Of Macrophages In the Metastasis Of Crcmentioning
confidence: 99%